2011
DOI: 10.1111/j.1095-8649.2011.03104.x
|View full text |Cite
|
Sign up to set email alerts
|

Two spinefoot colour morphs: mottled spinefoot Siganus fuscescens and white‐spotted spinefoot Siganus canaliculatus are synonyms

Abstract: Mottled spinefoot Siganus fuscescens and white-spotted spinefoot Siganus canaliculatus are two similar species that differ subtly in colouration and morphology. Three major mtDNA clades were identified for these species, but individuals were clustered by amplified fragment length polymorphism (AFLP) according to geography rather than morphology, suggesting that the colour morphs are interbreeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…In earlier studies of Elacatinus , Taylor and Hellberg (2005, 2006) suggested that, for this genus of 34 currently recognized species (Froese and Pauly 2013), speciation was consistent with a model of regional but recurrent adaptive radiations driven by a combination of colouration and ecological differentiation. However, we note that Hsu et al (2011) provide evidence that, at least in Siganus Forsskål, 1775, species defined by colour differences do not necessarily equate with genetic lineages.…”
Section: Introductionmentioning
confidence: 66%
“…In earlier studies of Elacatinus , Taylor and Hellberg (2005, 2006) suggested that, for this genus of 34 currently recognized species (Froese and Pauly 2013), speciation was consistent with a model of regional but recurrent adaptive radiations driven by a combination of colouration and ecological differentiation. However, we note that Hsu et al (2011) provide evidence that, at least in Siganus Forsskål, 1775, species defined by colour differences do not necessarily equate with genetic lineages.…”
Section: Introductionmentioning
confidence: 66%
“…canaliculatus and S . fuscescens morphotypes [ 20 ], and by non-concordance between morphotype and genetic clustering based on AFLP loci [ 21 ]. Authors have concluded that S .…”
Section: Introductionmentioning
confidence: 99%
“…fuscescens and S . canaliculatus interbreed, hence represent morphological variants or geographically isolated groups within a single biological species [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations